Perilaku Hidup Bersih Dan Sehat (PHBS) dalam Lingkungan Sekolah - Alam, Rizqy Iftitah (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Early childhood is the initial stage, where during this period the growth and development of children must be considered. This period is also very vulnerable to various kinds of health problems. Early childhood is also very sensitive to various external stimuli, so it is very easy to guide and provide an understanding of positive habits, including clean and healthy living habits. The implementation of clean and healthy living behaviors in the school environment will create a clean, healthy, comfortable environment, as well as being able to create health education and have great benefits in improving student welfare. SDN Paccinang 1 Makassar is one of the educational institutions where students do not understand how to implement clean and healthy living behaviors. They also still like to snack carelessly so that many students experience health problems, such as diarrhea. The objectives of this activity are: 1) Provide health education in the form of counseling activities on PHBS; 2) Provide demonstrations on how to wash hands properly and correctly. This activity was carried out at SDN Paccinang 1 Makassar. The methods used were counseling and demonstration. The results obtained from this activity are increased student knowledge about PHBS and students are able to do the right way to wash their hands. It is necessary to hold health counseling more often to improve health status towards a better direction.